The Impact of a Propose Training Program on the Coordination Elements of Beginner Soccer Players - Jamal Abu Bshara (My University, 2010)
The purposes of this study was to identify a suggested training program on the coordination elements for beginner soccer players. The paper is a content- based carried out and conducted on a sample of (40) beginner players from Paces Institution – Tubas 2009, the target age was from (9 – 12) year old players. Procedures: an empirical research of two groups was conducted over 8 weeks, three training sessions a week. Conclusion: the plan under discussion proved effective in achieving the stated goal. The results showed improvement in the various elements that ranged from - 14.16% to 104.84%. Recommendation: it is recommended that the propose model be adopted by the clubs, football training centers and any other institutions that focus on training 9-12 age groups. the propose model has a great deal to do with developing the coordination elements and thus the general performance of the player.

هدفت الدراسة التعرف إلى اثر برنامج تدريبي مقترح لتحسين مستوى القدرات التوافقية لدى ناشئ كرة القدم . وتكونت عينة الدراسة من (40) لاعبا مبتدئا في مؤسسة خطوات محافظة طوباس لعام 2009 م. وللفئة العمرية من (9-12) سنة، وقد اختيرت العينة بالطريقة العمدية، واستخدم الباحث المنهج التجريبي، وقد استغرق تطبيق البرنامج (8) أسابيع بواقع ثلاث وحدات أسبوعية . وأظهرت نتائج الدراسة إلى أن البرنامج التدريبي المقترح ذي فعالية في تحسين مستوى مكونات القدرات التوافقية المختلفة (القدرة على تقدير الوضع، القدرة على الربط الحركي، القدرة على بذل الجهد المناسب ، قدرة الحفاظ على التوازن، القدرة الإيقاعية، القدرة على الاستجابة السريعة، القدرة على التكيف مع الأوضاع المتغيرة)، و تراوحت نسبة التحسن بين القياسات القبلية والبعدية للمجموعة التجريبية ما بين ( -14.16% - 104.84%). يوصي الباحث باستخدام البرنامج المقترح من قبل جميع الأندية والمدارس الكروية والمؤسسات الرياضية التي تهتم بالفئة السنية قيد الدراسة لدوره الفعال في تطوير القدرات التوافقية وبالتالي تطوير الأداء عموما.
أثر برنامج تدريبي مقترح على تطوير مستوى القدرات التوافقية لدى ناشئ كرة القدم